Trafficking through the blood-brain barrier is directed by core and outer surface components of layer‐by‐layer nanoparticles - Nicholas G. Lamson; Andrew J. Pickering; Jeffrey Wyckoff; Priya Ganesh; Elizabeth A. Calle; Joelle P. Straehla; Paula T. Hammond (Wiley, 2024)
Abstract Drug‐carrying nanoparticles are a promising strategy to deliver therapeutics into the brain, but their translation requires better characterization of interactions between nanomaterials and endothelial cells of the blood-brain barrier (BBB). Here, we use a library of 18 layer‐by‐layer electrostatically assembled nanoparticles (NPs) to independently assess the impact of NP core and surface materials on in vitro uptake, transport, and intracellular trafficking in brain endothelial cells. We demonstrate that NP core stiffness determines the magnitude of transport, while surface chemistry directs intracellular trafficking. Finally, we demonstrate that these factors similarly dictate in vivo BBB transport using intravital imaging through cranial windows in mice. We identify that hyaluronic acid surface chemistry increases transport across the BBB in vivo, and flow conditions are necessary to replicate this finding in vitro. Taken together, these findings highlight the importance of assay geometry, cell biology, and fluid flow in developing nanocarriers for delivery to the brain.